THE EFFECT OF GOVERNMENT DEBT, ECONOMIC GROWTH, AND FISCAL INDEPENDENCE ON BUDGET DEFICIT IN LOCAL GOVERNMENTS IN BALI PROVINCE - I Gede Wiprada Pasupati; Ni Luh Putu Wiagustini; I Wayan Terimajaya (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This quantitative study employs a causal-explanatory design to examine the effects of public debt, economic growth, and fiscal autonomy on budget deficits across ten local governments in Bali Province. Utilizing a census-based approach on secondary panel data from audited Local Government Financial Reports (LKPD) and the Central Bureau of Statistics (BPS) over the 2020–2024 fiscal years, the hypotheses were tested via multiple linear regression analysis. The simultaneous test reveals that the independent variables highly significantly influence regional budget deficits, yielding an Adjusted R 2 of 89.1%. Partially, public debt exerts a positive and significant effect on the deficit, signaling a debt overhang condition and a deficit-debt spiral that constricts fiscal space. Conversely, economic growth exhibits a negative but non-significant trajectory due to pro-cyclical spending policies and structural expenditure rigidities. Meanwhile, fiscal autonomy has a negative and significant impact on mitigating deficits, demonstrating that optimizing local own-source revenue (PAD) serves as a resilient fiscal buffer against financial distress. To ensure long-term fiscal sustainability, local governments in Bali are advised to enhance expenditure efficiency, direct public debt strictly toward productive investments, and proactively expand their own-source revenue base.